Tidal range technologies and state of the art in review. (June 2016) - Waters, Shaun; Aggidis, George
Abstract: Tidal range technology has seen much development and interest in recent years. The times when a barrage scheme would be rejected due to environmental and cost concerns is coming to an end. A large variety of new lower cost and less invasive methods have since emerged in the forms of tidal lagoons, reefs and fences. Since the construction of La Rance in 1967, advancements in turbine technologies and design has since resulted in a plethora of new, exciting turbine designs for tidal energy. A selection of new turbines with possible tidal range applications includes the modified bulb turbine with two sets of guide vanes, a counter-rotating turbine, Archimedes screw and a gyro device. However, the same design is continuously being chosen – the Kaplan bulb turbine. Through the use of a marking criterion covering key aspects that should be considered when choosing a turbine a variety of the new designs available are investigated. The key aspects researched include, environmental effects, the two-way efficiency, initial costs and maintenance costs/difficulty.